2013
DOI: 10.1002/jmrs.21
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of author productivity in international radiography journals 2004–2011

Abstract: IntroductionRadiography, the allied health profession, has changed beyond recognition over the last century; however, in academic terms radiography is a relatively young profession. It is therefore still establishing its professional knowledge base. This article uses peer-review author productivity distribution to evaluate its scholarly maturity.MethodsFour peer-reviewed journals in medical radiation sciences were examined over an 8-year period (2004–2011) and author productivity was compared to Lotka's law. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
54
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 24 publications
2
54
0
Order By: Relevance
“…This transition period is certainly extended if academic radiographers are to lead research and supervise doctorate (PhD) students as part of their role. Radiography is considered to be a young academic profession 1 and as such the route in for many radiographers is via a background in clinical practice; in more traditional academic disciplines, the completion of a PhD and one or more post-doctoral positions is the norm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This transition period is certainly extended if academic radiographers are to lead research and supervise doctorate (PhD) students as part of their role. Radiography is considered to be a young academic profession 1 and as such the route in for many radiographers is via a background in clinical practice; in more traditional academic disciplines, the completion of a PhD and one or more post-doctoral positions is the norm.…”
Section: Introductionmentioning
confidence: 99%
“…A requirement for all radiography academics to undertake research would help to support realisation of the SCoR research strategy, although this will take time and a significant commitment from the HE sector. As radiography is still a young academic profession and there are relatively few radiographers holding PhDs and undertaking research compared to other professions, 1,7,16 there is a need to develop the academic workforce to a point where research in radiography can not only be supported, but can flourish 9 . The evidence in this survey regarding the amount of research time afforded to academic radiographers in the UK suggests that many…”
mentioning
confidence: 99%
“…Evidence for the growth of radiography research has also emerged from four recent bibliometric studies which reviewed the productivity of radiography authors and their institutions by analysis of specific imaging-related journals [6][7][8] or by using an electronic search tools to target named authors. 9 While the analyses were each performed in different ways with different strengths and limitations, they all confirmed that radiography publication activity is increasing year on year, but that the majority of articles emerge from a small number of authors and centres.…”
Section: Editorialmentioning
confidence: 99%
“…More than 2,000 unique authors of research published in radiography journals between 2004 to 2013, yet more than three quarters contributed to just one article. 7 Less than 10% of authors published more than two papers in eight years; 7 these more productive authors were usually academics, engaging in regular co-authorship within and outside their institution. The study by Ekpo et al showed that some departments are managing to effectively combine radiography research and teaching, with several publications from several different staff each year, 9 however the majority of radiography departments have few publications annually, from only one or two staff.…”
Section: Editorialmentioning
confidence: 99%
“…While radiography and the allied health care professions have changed beyond recognition over the last century, only entering the university sector in the 1990s, radiography is still relatively young in academic terms (Snaith, 2013). Radiography is still in need of developing and identifying theoretical and methodological views of the discipline in order to clarify the research interests and perspectives, and sharpen the philosophical arguments for justifying radiography as an independent academic discipline (Ahonen & Liikanen, 2009).…”
Section: Introductionmentioning
confidence: 99%